2018
DOI: 10.1364/josab.35.000958
|View full text |Cite
|
Sign up to set email alerts
|

Carrier-envelope phase effects in graphene

Abstract: We numerically study the interaction of a terahertz pulse with monolayer graphene. We observe that the electron momentum density is affected by the carrier-envelope phase (CEP) of the single to few-cycle terahertz laser pulse that induces the electron dynamics. In particular, we see strong asymmetric electron momentum distributions for non-zero values of the CEP. We explain the origin of the asymmetry within the adiabatic-impulse model by finding conditions to reach minimal adiabatic gap between the valence ba… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 48 publications
(77 reference statements)
0
8
0
Order By: Relevance
“…A non-adiabatic transition from the valence to the conduction band corresponds to a "flip" of the sublattice pseudospin [17,30]. This dynamical interband process may result in a finite conduction band population after the passage of the pulse [3,18], a population which can then be probed using time-resolved ARPES [13,[15][16][17]. An alternative way of describing this physical process is that, for a given quasiparticle momentum p, the valence and conduction band of graphene behave like a driven two-level atom.…”
Section: Problem Definitionmentioning
confidence: 99%
See 2 more Smart Citations
“…A non-adiabatic transition from the valence to the conduction band corresponds to a "flip" of the sublattice pseudospin [17,30]. This dynamical interband process may result in a finite conduction band population after the passage of the pulse [3,18], a population which can then be probed using time-resolved ARPES [13,[15][16][17]. An alternative way of describing this physical process is that, for a given quasiparticle momentum p, the valence and conduction band of graphene behave like a driven two-level atom.…”
Section: Problem Definitionmentioning
confidence: 99%
“…The result of momentum-resolved experiments with graphene has been the subject of several articles in recent years, most of which consider the effect of a short optical or THz pulse on the conduction band population in reciprocal space [3,13,16,[18][19][20]. Theoretical investigations have revealed that the details of the temporal pulse shape, for instance the carrier-envelope phase, can have a manifest impact on the momentum space patterns [3,13]. In this article, we consider the inverse problem, * steve.maclean@uwaterloo.ca namely finding the temporal pulse shape which minimizes the photo-induced carrier density in graphene over a predefined momentum window.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamics of charge carriers in graphene subjected to electromagnetic fields has gained momentum in the last few years, with the potential of controlling the electron dynamics in graphene-based devices [20][21][22][23]. Many theoretical and experimental investigations have focused on the interaction of graphene with a (homogeneous) laser field [24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…As transient EMD is a practical probe experimentally 23,24 , this suggests a way in which the LZS physics may be directly observed in 2d materials, opening the way to correlate indirect LZS physics such as induced currents with the fundamental momentum space interference patterns. In contrast to previous works that have employed simple single particle tight-binding Hamiltonians to study the LZS effect 3,20,21,[25][26][27][28][29] , we will here deploy the time dependent version of density functional theory (TD-DFT). To establish the accuracy of the EMD as a record of LZS interference we compare it with the excited electron distribution, N ex , defined within TD-DFT as 30 :…”
mentioning
confidence: 99%